Energy Efficient Rare Earth Lifting Permanent Magnet. Issue 2 (May 2019) - Ding, N; Liu, C; Duan, J S; Jiang, S N; Hou, Y Q
Abstract: Nowadays lifting electromagnet is widely used in the world, but its fatal disadvantages are related to the electrical power input. A novel and energy efficient Rare Earth lifting permanent magnet is presented, which can completely overcome the lifting electromagnet disadvantages. In this paper, first, the developed optimization magnetic circuit design rule for Rare Earth lifting permanent magnet is discussed. Second, the lifting permanent magnet magnetic circuit design procedure is introduced. Finally, the invented mechanical drive system is expatiated. Industry prototype is manufactured, and it verifies that the proposed Rare Earth lifting permanent magnet is feasible.